2008
DOI: 10.1111/j.1440-1681.2008.04845.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐oxidant Activity Mediated Neuroprotective Potential of Trimetazidine on Focal Cerebral Ischaemia–reperfusion Injury in Rats

Abstract: 1. The present study was designed to investigate the neuroprotective effect of trimetazidine (TMZ) following focal cerebral ischaemia-reperfusion (I/R) injury in rat forebrain. 2. Cerebral I/R injury was induced in rats by middle cerebral artery occlusion (MCAO) for 2 h, followed by reperfusion for 22 h. Trimetazidine (5 and 25 mg/kg, i.p.) was administered 1 h after induction of MCAO. The effects of TMZ were investigated by measuring neurological deficit, volume of infarct and brain swelling after 22 h reperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…In addition to natural extracts, studies have found that commonly used cardiovascular drugs such as simvastatin (transfusion of lipids) and trimetazidine (anti-angina drugs) have anti-CIRI effects, and that the mechanism involves anti-oxidative activity (Dhote and Balaraman, 2008;Beretta et al, 2011;Anthony Jalin et al, 2015). Lipophilic simvastatin can significantly improve the antioxidant capacity of ischemic brain tissue, while hydrophilic simvastatin has no obvious brain protection properties (Beretta et al, 2011), suggesting that increasing bloodcerebrospinal fluid barrier permeability could be an effective way to improve the treatment of CIRI with existing drugs.…”
Section: Synthetic Antioxidantmentioning
confidence: 99%
“…In addition to natural extracts, studies have found that commonly used cardiovascular drugs such as simvastatin (transfusion of lipids) and trimetazidine (anti-angina drugs) have anti-CIRI effects, and that the mechanism involves anti-oxidative activity (Dhote and Balaraman, 2008;Beretta et al, 2011;Anthony Jalin et al, 2015). Lipophilic simvastatin can significantly improve the antioxidant capacity of ischemic brain tissue, while hydrophilic simvastatin has no obvious brain protection properties (Beretta et al, 2011), suggesting that increasing bloodcerebrospinal fluid barrier permeability could be an effective way to improve the treatment of CIRI with existing drugs.…”
Section: Synthetic Antioxidantmentioning
confidence: 99%
“…SOD converts superoxide into oxygen and hydrogen peroxide. Similar to glutathione, many treatments that ameliorate stroke damage are accompanied by an increase in SOD [113, 114]. Furthermore, rodents overexpressing SOD1 have significantly smaller injuries after both focal and global ischemia [115, 116], while mice with decreased SOD1 have larger infarcts [117].…”
Section: Astrocyte Support Of Neurons After Strokementioning
confidence: 99%
“…Recently, some reports indicate the neuroprotective effects of trimetazidine in various experimental models. These effects have been suggested to be due to its antioxidant property (Mironovan et al 2001;Dhote and Balaraman 2008;Serarslan et al 2009). Baltalarli et al (2000) and Iqbal et al (2002) showed that administration of trimetazidine during the period of ischemia-reperfusion injury reduced the number of damaged cells in cerebral tissue and preserved neurological function in transient global ischemia model in rats and gerbils, respectively.…”
Section: Introductionmentioning
confidence: 95%